DECENTRALIZED AUTONOMOUS NETWORKS FOR SECURE DATA SHARING: A THEORETICAL FRAMEWORK AND CONCEPTUAL ANALYSIS - Shaikh, Mohammad Shahnawaz; Chauhan, Prithviraj S; Baig, Imran; Ali, Syed Ibad (COMPUSOFT: An International Journal of Advanced Computer Technology, 2023)
In the era of data-driven decision-making, secure data sharing is critical for ensuring privacy and integrity. This paper explores the concept of decentralized autonomous networks (DANs) as a solution for secure data sharing. We propose a theoretical framework for DANs, highlighting their potential to enhance data security through decentralization and autonomy. The paper presents conceptual models, theoretical analysis, and example scenarios to demonstrate the effectiveness and feasibility of DANs in secure data sharing.